(untitled) - Sylva Bártlová; Ivana Chloubová; Valérie Tóthová; Věra Hellerová; Jana Kimmerová; František Dolák; Olga Shivairová; David Kimmer; Aleš Chrdle (Central European Journal of Nursing and Midwifery, 2023)
Aim: The study aimed to describe nurses' roles, map their views, knowledge, and experiences, and clarify the factors influencing their work and personal life during the Covid-19 pandemic in the Czech Republic. Design: A descriptive and cross-sectional design was used for the study. Methods: A representative sociological survey was conducted. A non-standardized questionnaire was used to collect data; the primary objective was to survey nurses' views, knowledge, and experiences gained during the Covid-19 pandemic and identify essential issues that must be addressed before the next pandemic. The questionnaire contained a total of 57 questions. The sample was constructed by quota sampling; the criteria for inclusion in the sample were the respondents' gender, age, and region. These characteristics were established as representative. The sample consisted of 1,197 nurses. Results: The most commonly reported factor influencing the work of nurses during the Covid-19 pandemic was fear of transmitting the infection (63.6%). Fear of the unknown (59%) and increased workload (54.7%) were also frequently reported to be strong influencers. The responses of nurses were statistically significantly influenced by the type of medical facility in which they worked (p < 0.05) and where they worked during the Covid-19 pandemic (p < 0.001). Most respondents (89.6%) said Covid-19 represented increased physical and mental burdens. Almost the same proportion of respondents (88.4%) felt Covid-19 affected their social lives, and 76.7% reported that it also affected their personal lives. Conclusion: Healthcare facility management should ensure sufficient personal protective equipment (PPE) is available before pandemics and pay close attention to the needs of staff regarding psychological counselling and crisis intervention during pandemics.